2020
DOI: 10.18203/2319-2003.ijbcp20201749
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary tract infection and sensitivity pattern amongst children less than 3 years of age with fever in a tertiary care hospital in South Karnataka

Abstract: Background: Antimicrobial resistance is a major concern especially in urinary tract infections in children as improperly treated urinary tract infections (UTIs) on long term can cause renal scarring in young children, which leads to long term morbidities like hypertension, chronic renal disease and pre-eclampsia. The empirical therapy for UTI varies regionally due to their varied sensitivities and resistance pattern. This study aims to facilitate policy making in empirical antibiotic therapy of pediatric patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(12 reference statements)
3
2
0
Order By: Relevance
“…In contrast, Ahmadzadeh et al [10] reported a higher incidence of abnormalities (60.6%), as majority (77%) of their study group were children aged less than 5 years. The most common abnormality detected in our study was VUR, which was similar to other studies [9][10][11][12]16], of which 37.5% (3/8) had bilateral VUR. similar results obtained by other studies are compiled in Table 3.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, Ahmadzadeh et al [10] reported a higher incidence of abnormalities (60.6%), as majority (77%) of their study group were children aged less than 5 years. The most common abnormality detected in our study was VUR, which was similar to other studies [9][10][11][12]16], of which 37.5% (3/8) had bilateral VUR. similar results obtained by other studies are compiled in Table 3.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, fever was the most common presenting symptom (86%) which was similar to the studies done by Ahmadzadeh et al [10] (83%) and Ponvelil et al (74.2%) [11]. Urinary symptoms were seen in only 14%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sensitivity of E. coli to cefotaxime in our study was similar to study by Badhan et al 22 In contrast study done by Patel et al and Ponvelil et al E. coli was found most sensitive to imipenem and nitrofurantoin. 23,24 In our study E. coli was highly resistance to cefepime, cefurorixme, cefixime, gentamycin, ampicillin and amoxicillin. In contrast other study shows high resistance to fluroquinolones.…”
Section: Resultsmentioning
confidence: 56%
“…In our study, there were 11 (15.5%) males and 60 (84.5%) females. Female predominance is mostly because of its short urethra [5] [25] found only 33.3% sensitivity to Amikacin. The sensitivity pattern of drugs is changing and due to rational use of the antibiotics the uropathogens are becoming resistant to multiple drugs.…”
Section: Discussionmentioning
confidence: 99%